1991
DOI: 10.1111/j.1524-4725.1991.tb03976.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Cutaneous Neoplasms: Clinicopathologic Correlation

Abstract: Recently, magnetic resonance imaging (MRI) has been reported to be clinically useful, in selected cases, in patients with melanocytic skin lesions. This report describes good resolution, clinically useful MRI scans of squamous cell carcinoma, dermatofibroma, and primary cutaneous B-cell lymphoma. The tumor depth measured by MRI was in excellent correlation with Breslow's depth measurements, indicating that MRI is probably the radiologic technique of choice for preoperative evaluation of the extent and depth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 25 publications
(37 reference statements)
2
21
0
Order By: Relevance
“…Expressed in terms of voxel size, the resolution achieved is an order of magnitude higher than reported in prior work. At a voxel size on the order of 2 x lo-'' mm3 an SNR of [5][6][7][8][9][10] in the dermis and Gradient-echo ROI signal versus echo time in the dorsal calf (156 x 936 x 1,500 pm3 voxel size; smallest dimension perpendicular to the skin surface). The solid line for the dermis was obtained by fitting the data to a sum of two exponentials (T2* = 9.8 ms, 91 % and 42.7 ms, 9%).…”
Section: Discussionmentioning
confidence: 99%
“…Expressed in terms of voxel size, the resolution achieved is an order of magnitude higher than reported in prior work. At a voxel size on the order of 2 x lo-'' mm3 an SNR of [5][6][7][8][9][10] in the dermis and Gradient-echo ROI signal versus echo time in the dorsal calf (156 x 936 x 1,500 pm3 voxel size; smallest dimension perpendicular to the skin surface). The solid line for the dermis was obtained by fitting the data to a sum of two exponentials (T2* = 9.8 ms, 91 % and 42.7 ms, 9%).…”
Section: Discussionmentioning
confidence: 99%
“…The first cross-sec tional images of the skin in vivo obtained by MR imaging were presented by our reserarch team in Liège during the Symposium on Bioengineering and the Skin in 1986 [13]. Since this date, different research teams have written about in vivo MR imaging of normal [14][15][16] and pathologic skin [17,18]. MR imaging is also available for characterizing the skin by the measurement of relaxation times in the different skin layers as it may give information about the physicochemical prop erties of the skin in vivo [19].…”
Section: Introductionmentioning
confidence: 99%
“…ZEMTSOV et al (21) reported that, according to good clinico-pathological correlations observed in 5 patients, MR imaging may be useful in melanotic skin lesions. Although their spatial resolution was not as good as that used in the present study, the authors obtained clinically helpful images of squamous cell carcinomas, dermatofibromas, and primary cutaneous B-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%